Vasculocentric Axonal NfH in Small Vessel Disease. Issue 3 (27th January 2022) - Anad, Adam; Barker, Miriam K; Katanga, Jessica A; Arfanakis, Konstantinos; Bridges, Leslie R; Esiri, Margaret M; Isaacs, Jeremy D; Prpar Mihevc, Sonja; Pereira, Anthony C; Schneider, Julie A; Hainsworth, Atticus H
Abstract: Cerebral small vessel disease (SVD) causes lacunar stroke and vascular cognitive impairment in older people. The pathogenic pathways from vessel pathology to parenchymal damage in SVD are unknown. Neurofilaments are axonal structural proteins. Neurofilament-light (NfL) is an emerging biomarker for neurological disease. Here, we examined the high molecular weight form neurofilament-heavy (NfH) and quantified a characteristic pattern of peri-arterial (vasculocentric) NfH labeling. Subcortical frontal and parietal white matter from young adult controls, aged controls, and older people with SVD or severe Alzheimer disease (n = 52) was immunohistochemically labeled for hyperphosphorylated NfH (pNfH). The extent of pNfH immunolabeling and the degree of vasculocentric axonal pNfH were quantified. Axonal pNfH immunolabeling was sparse in young adults but a common finding in older persons (controls, SVD, or AD). Axonal pNfH was often markedly concentrated around small penetrating arteries. This vasculocentric feature was more common in older people with SVD than in those with severe AD (p = 0.004). We conclude that axonal pNfH is a feature of subcortical white matter in aged brains. Vasculocentric axonal pNfH is a novel parenchymal lesion that is co-located with SVD arteriopathy and could be a consequence of vessel pathology.